Situation Report: Czechoslovakia, 20 December 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Charter 77 Protests Czechoslovak Media's "Disinformation" World Marxist Review Conference in Prague What Vasil Bilak Said at the World Marxist Review Conference Economic Prospects for 1985 The 10th Congress of Agricultural Cooperatives "Young People of the CSSR" Write to Husak Again Jewish Religious Communities Cultural Problems That Will Not Lie Down